Effectiveness of Emotional Schema Therapy on the Quality of Relationship Dimensions and Conflict Resolution Styles in Betrayed Spouses - Eslahi Farshami, Fatemeh (Applied Family Therapy Journal (AFTJ), 2025)
Objective: This study aimed to evaluate the effectiveness of Emotional Schema Therapy (EST) in improving relationship quality and conflict resolution styles among betrayed spouses.Methods: This study was conducted as a randomized controlled trial (RCT) with 30 participants from Tehran, Iran, who were recruited through counseling centers and online advertisements. Participants were randomly assigned to either the experimental group (15 participants), which received eight weekly 90-minute EST sessions, or the control group (15 participants), which did not receive any therapeutic intervention during the study period. Data were collected at three time points: pre-test, post-test, and five-month follow-up, using standardized measures of relationship quality and conflict resolution styles. Repeated measures analysis of variance (ANOVA) and Bonferroni post-hoc tests were used to analyze the data using SPSS version 27.Findings: The results indicated significant improvements in both relationship quality and conflict resolution styles in the experimental group compared to the control group. For relationship quality, repeated measures ANOVA revealed a significant interaction effect between time and group (F(2, 54) = 82.46, p < .001). Similarly, for conflict resolution styles, a significant interaction effect was observed (F(2, 54) = 76.92, p < .001). Bonferroni post-hoc tests showed that these improvements were sustained at the five-month follow-up.Conclusion: Emotional Schema Therapy is an effective intervention for enhancing relationship quality and conflict resolution styles in betrayed spouses. By targeting maladaptive schemas and promoting emotional regulation, EST provides a comprehensive framework for addressing relational challenges following infidelity. These findings support the integration of EST into marital therapy practices.